ANALISIS KUALITAS APLIKASI MOBILE ANDROID TIKTOK MENGGUNAKAN METODE MCCALL - Vincent Andreson; Marvin Junaidi; Niko Ananda Limmanto; Mario Aldy Wijaya; Kevin Brillian; Dicky Pratama (CV. Denasya Smart Publisher, 2026)
Software quality is a crucial aspect in mobile application development, particularly for social media applications with high user interaction and intensive usage. TikTok, as one of the most widely used short-video-based social media applications, requires optimal operational quality to ensure a satisfactory user experience. This study evaluates the quality of the TikTok Android application using the McCall method, focusing on Product Operation factors. A quantitative approach was employed, with data collected through questionnaires distributed to TikTok users. The analyzed quality factors include correctness, reliability, efficiency, integrity, and usability. Data were analyzed using weighted scoring based on the McCall model to determine the overall quality level. The results indicate that the TikTok Android application is in the good category, with correctness (84.2%) and efficiency (75%) scoring highest. However, reliability (50.4%), integrity (51.8%), and usability (52.6%) were rated fair, indicating areas for improvement. This study provides insights for developers to enhance software quality and serves as a reference for future research on mobile social media application evaluation.